Appropriateness of urine culture requests in primary care in Spain: A cross-sectional descriptive study - Silvia Fernández-García; Ramon Monfà; Cristina Miranda Jiménez; Maria Giner-Soriano; Frederic Gómez; Ana Moragas (Atención Primaria)
Objective: Studies evaluating urine culture requests in our country have highlighted a high rate of requests that fall outside the indications specified in clinical guidelines. We evaluated the current degree of inadequacy in the request of urine cultures and how this influences the therapeutic decisions of general practitioners. Design: Cross-sectional descriptive study. Setting: Three primary care centres in Tarragona area. Participants: Urine culture requests from the adult population ≥ 18 years old, received at the Microbiology Service of the reference hospital in 2022. All requests were made in primary care settings. Main measures: The collected variables included sociodemographic data, urinary tract infection (UTI) symptoms at the time of the urine culture request, comorbidities, reason for the request (including diagnosis), type of urine culture, therapeutic approach before and after receiving the result, and the urine culture result. Results: A total of 461 urine cultures were reviewed: 152 men (mean age 64.1 years) and 309 women (mean age 57 years). Of the urine cultures analyzed, 17.4% were for cystitis (22% in women), 2.4% for pyelonephritis, 1.3% for complicated UTIs, and 1.5% for asymptomatic bacteriuria. In 10.6%, they were for recurrent UTIs; in 9.6%, post-treatment. In 55.5% of cases, general practitioners continued without antibiotic treatment, regardless of urine culture results. The reason to request was unknown in 18.9%. Antibiotic changes occurred in 5.6%. Conclusions: There is still a high rate of urine culture over-requesting in primary care, with 20% of cultures being ordered for otherwise uncomplicated UTIs. While the methodology of the project does not allow for causal analysis, it provides a detailed description of clinical practices in primary care. Resumen: Objetivo: Los estudios dirigidos a evaluar las solicitudes de urocultivos en nuestro país han puesto de manifiesto una alta tasa de solicitudes de urocultivos fuera de las indicaciones de las guías clínicas. Evaluamos el grado actual de inadecuación y cómo esto influye en la decisión terapéutica de los médicos de familia. Diseño: Estudio descriptivo transversal. Emplazamiento: Tres centros de salud en Tarragona. Participantes: Peticiones de urocultivos de población adulta ≥18 años recibidas en el Servicio de Microbiología del hospital de referencia en 2022. Todas las solicitudes se pidieron en atención primaria. Mediciones principales: Las variables incluyeron datos sociodemográficos, síntomas de infección del tracto urinario (ITU) en el momento de su petición, comorbilidades, motivo (incluido el diagnóstico), tipo de urocultivo, manejo terapéutico antes y después de recibir el resultado y el resultado del urocultivo. Resultados: Se revisaron 461 urocultivos: 152 hombres (edad media 64,1 años) y 309 mujeres (edad media 57 años). De los urocultivos analizados, el 17,4% fueron por cistitis (22% en mujeres), el 2,4% por pielonefritis, el 1,3% por ITU complicadas y el 1,5% por bacteriuria asintomática. En el 10,6% fueron por ITU recurrentes; en el 9,6%, post-tratamiento. En el 55,5% de los casos, los médicos continuaron sin tratamiento antibiótico, independientemente de los resultados de los urocultivos. El motivo para pedir urocultivos fue desconocido en el 18,9%. Los cambios en el tratamiento antibiótico se observaron en el 5,6%. Conclusiones: Todavía hay una alta tasa de solicitud de urocultivos en atención primaria, con un 20% de los cultivos solicitados para infecciones urinarias no complicadas. La metodología del proyecto no permite un análisis causal, pero sí una descripción de la práctica clínica en atención primaria.